UJI EFEK ANTIINFLAMASI EKSTRAK ETANOL KULIT BATANG JAMBU BIJI (PSIDIUM GUAJAVA) TERHADAP EDEMA KAKI TIKUS JANTAN GALUR WISTAR - Lanti, Deliyana; Fatimawali, Fatimawali; Wullur, Adeanne (PHARMACON, 2012)
Inflamation is a protective response of body from injury of cell. Edema is one ofinflammation sign. Guava stem leather contains of flavonoid which has potency to inhibitedema. The aims of this research were to study antiinflamation effect of ethanolic extractofguava stem leather (Psidium guajava L.) on edema of white mice strain wistar legs.Thesubjects in this research were 25 wistar male which divided into 5 groups, namely negativecontrol (aquades), positive control (indometasin) and extract group with concentration 1%,2% and 4%. Every group consists of five mices. Aquades, indometasin and extractsupplementation were done per oral, followed with 5% of white egg induction on mice leftleglead to edema formation.Measurement of edema volume was done using plestimometer,and observation of edema were made every hour during 7 hours. Data which obtained wereanalyzed with ANOVA, if there is a differences between treatment, analysis continue to LSDtest. The result shows that supplementation of ethanolic extract of guava stem leatherconcentration 1% and 2 % decrease edema significantly with percent of inhibition 37,37 and32,59%, but supplementation of ethanolic extract of guava stem leather concentration 1% didnot shows inhibition effect .Keywords: guava stem leather, antiinflamation, edema